Arid Land Systems: Sciences and Societies - Ahearn, Ariell (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Understanding deserts and drylands is essential, as arid landscapes cover >40% of the Earth and are home to two billion people. Today's problematic environment-human interaction needs contemporary knowledge to address dryland complexity. Physical dimensions in arid zones-land systems, climate and hazards, ecology-are linked with social processes that directly impact drylands, such as land management, livelihoods, and development. The challenges require integrated research that identifies systemic drivers across global arid regions. Measurement and monitoring, field investigation, remote sensing, and data analysis are effective tools to investigate natural dynamics. Equally, inquiry into how policy and practice affect landscape sustainability is key to mitigating detrimental activity in deserts. Relations between socio-economic forces and degradation, agro-pastoral rangeland use, drought and disaster and resource extraction reflect land interactions. Contemporary themes of food security, conflict, and conservation are interlinked in arid environments. This book unifies desert science, arid environments, and dryland development. The chapters identify land dynamics, address system risks and delineate human functions through original research in arid zones. Mixed methodologies highlight the vital links between social and environmental science in global deserts. The book engages with today's topical themes and presents novel analyses of arid land systems and societies.